FOREIGN INVESTMENT MULTINATONAL COMPANIES AND ECONOMIC DEVELOPMENT - Popov, Đorđe (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
There is no universal answer on the question whether foreign investments stimulate economic development. The positive effect of foreign direct investments will follow when the investments is carried out under normal conditions of competition. That means, above all, low barriers for foreign trade and the low level of restrictions for foreign owned companies. In such circumstances, multinational corporations can assist the economies of penetration to make its businesses more efficient. Foreign investors bring with them brand new types of economic activities and in that way shifting the limits of business opportunities in the countries of penetration. But if the investments are implemented in markets protected with protectionist barriers of various kinds, then they could have negative effects. The negative effects are in particularly reflected in the inefficient use of domestic resources. Foreign investments depend on the macro and micro institutional reforms, low inflation, real exchange rate, and reasonably efficient legal system that protects the property rights and encourages savings and investment. The low level of corruption, together with the foregoing conditions is a prerequisite for the creation of a stimulating environment for foreign investments.